DETERMINATION OF PILE BRINGING CAPACITY USING SEISMIC SHOCK TEST METHOD IN THE KATARAJA TOLL ROAD DEVELOPMENT PROJECT - Sitompul, Miranda
Pile is one part of the construction used to withstand the load from the top of the building structure to the soil layer. The pile type depends on the building above it, because each pile has its carrying capacity and uses. There are faults in some piles after installation in many locations because the geotechnical conditions and soil structure facing the piles are not suitable. This can be avoided by checking using the Seismic Shock Test (SST) method, namely Non-Destructive Evaluation (NDE) by utilizing 1-dimensional seismic waves originating from knocking on the pile head using a hammer. The piles tested in this study are hollow. In principle, SST uses two accelerometers, the first accelerometer is mounted on the hammer to record the force, and the second accelerometer is placed at the head of the pile to record the speed of the waves traveling along the pile. The difference in impedance between the pile and the ground around the pile causes some waves to be transmitted into the ground and some waves to be reflected by the pile head. The data obtained are velocity and force waves in the time domain. Data processing and analysis were carried out with Fast Fourier Transform using MATLAB. The velocity wave is then divided by the FFT force wave, generating a mobility curve. The pile length obtained is 11.236 m, and the carrying capacity of the pile is 75.284 kN/m.